2016
DOI: 10.1097/hjh.0000000000000887
|View full text |Cite
|
Sign up to set email alerts
|

Centrally acting drug moxonidine decreases reactive oxygen species via inactivation of the phosphoinositide-3 kinase signaling in the rostral ventrolateral medulla in hypertensive rats

Abstract: The centrally antihypertensive drug moxonidine decreases ROS production in the RVLM through inactivation of the PI3K/Akt signaling pathway in hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 56 publications
0
18
1
Order By: Relevance
“…It is reported that the activity of the PI3K/AKT pathway is enhanced in the RVLM of SHR, and the phosphorylation of AKT in the PVN of hypertensive rats is also increased . Recently, we also confirmed that an inactivation of PI3K signaling in the RVLM is involved in antioxidative stress induced by central antihypertensive mechanism . However, the present data does not address the question how ACE2 reduces the production of proinflammatory cytokines via an inactivation of PI3K signaling.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…It is reported that the activity of the PI3K/AKT pathway is enhanced in the RVLM of SHR, and the phosphorylation of AKT in the PVN of hypertensive rats is also increased . Recently, we also confirmed that an inactivation of PI3K signaling in the RVLM is involved in antioxidative stress induced by central antihypertensive mechanism . However, the present data does not address the question how ACE2 reduces the production of proinflammatory cytokines via an inactivation of PI3K signaling.…”
Section: Discussioncontrasting
confidence: 70%
“…It has been demonstrated that the PI3K signaling in the RVLM is upregulated in hypertension, and its inactivation leads to reduction in reactive oxygen species (ROS) production and cardiovascular function . Moreover, we recently report that gene knockdown of the PI3K subunit p110δ in the RVLM exerts the centrally antihypertensive action .…”
Section: Introductionmentioning
confidence: 96%
“…This further suggested the relevance of the simultaneous activation of I 1 /I 2 -IRs to dampen neurotoxic signalling induced by KA in mice (especially in the hippocampus). However, and contrary to the observed effect of efaroxan preventing the hypothermic response of moxonidine, the acute inhibitory effects of LSL61122 and moxonidine on hippocampal p35/p25 cleavage were not antagonised by idazoxan (against LSL61122) or by efaroxan (against moxonidine), as it was expected for these commonly used I 2 -or I 1 -IR antagonists (see Cambridge and Robinson, 2005;Edwards and Ernsberger, 2003;Garau et al, 2013;Sánchez-Blázquez et al, 2000;Wang et al, 2016). In fact, idazoxan has previously been shown to inhibit calpaindependent cleavage of spectrin α upon glutamate treatment through reversible blockade of NMDAR-mediated Ca 2+ influx in vitro (Jiang et al, 2010), to induce hypothermia and neuroprotection in an ischemia model in rats (present study; Craven and Conway, 1997) and to modulate immunoreactive IR proteins in the mouse brain (Keller and García-Sevilla, 2015a).…”
Section: Discussionmentioning
confidence: 66%
“…Superoxide generation was determined by fluorescent-labelled dihydroethidium (DHE, Molecular Probes) staining as previously described [22,28]. Protein immunofluorescence staining was performed as previously described [21,29].…”
Section: Immunohistochemistry and Immunofluorescence Studiesmentioning
confidence: 99%
“…Measurement of RVLM protein was performed as previously described [28,30]. Briefly, protein extracted from the RVLM was used for measurements of TNF-α, the 67-kDa isoform of glutamate decarboxylase (GAD67), atrial natriuretic peptide (ANP), beta-myosin heavy chain (β-MHC), NAD(P)H oxidase subunit NOX 2 (gp91 phox ) and NOX 4 (Santa Cruz Biotechnology Inc, Santa Cruz, California) expressions by western blot.…”
Section: Western Blottingmentioning
confidence: 99%